2018
DOI: 10.4049/jimmunol.1701447
|View full text |Cite
|
Sign up to set email alerts
|

CD8α+CD11c+ Extracellular Vesicles in the Lungs Control Immune Homeostasis of the Respiratory Tract via TGF-β1 and IL-10

Abstract: The immune balance of the respiratory tract is strictly regulated. Extracellular vesicles (EVs) have been reported to participate in maintaining the immune balance in the intestinal tract, but whether they are involved in regulation of the immune balance in the respiratory tract has yet to be revealed. In this study, we found that physiological EVs from lungs of WT mice (L-EVs) could be isolated, which contained the immunosuppressive cytokines TGF-β1 and IL-10. Among L-EV subsets, only the CD8αCD11c EV subset … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 48 publications
(51 reference statements)
0
12
0
Order By: Relevance
“…Wan et al investigated the effects of EVs from healthy mouse lungs in regulation of the immune balance in the respiratory tract. They found that, among the subsets of EVs, CD8α+ CD11c+ EVs contain immunosuppressive cytokines TGF‐β1 and IL‐10.…”
Section: Resultsmentioning
confidence: 99%
“…Wan et al investigated the effects of EVs from healthy mouse lungs in regulation of the immune balance in the respiratory tract. They found that, among the subsets of EVs, CD8α+ CD11c+ EVs contain immunosuppressive cytokines TGF‐β1 and IL‐10.…”
Section: Resultsmentioning
confidence: 99%
“…The cochlea is surrounded by the otic vesicle that gradually ossi es and becomes rigid as the mouse ages, especially after P10, and this makes it di cult to dissect the basilar membrane for extracting cochlear tissue-derived sEVs. Some recent studies have used enzyme digestion for the purpose of maintaining the integrity of the cells as much as possible in order to extract EVs from fat, brain, and tumor tissues [35,[83][84][85][86], while other studies have ground the tissues as a necessary step for extracting EVs [85,[87][88][89]. Crescitelli et al showed that the digestive enzymes in the existing tissue extraction methods are ineffective for bone tissue, and the methods for this type of tissue need further optimization [90].…”
Section: Discussionmentioning
confidence: 99%
“…EVs isolated from the lungs of mice have also been shown to contain the anti-inflammatory cytokines TGFβ-1 and IL-10. These EVs likely originate from dendritic cells that can communicate with T cells to inhibit their proliferation in response to a specific antigen [ 122 ]. There is also evidence that immune cell-derived EVs are involved in tissue remodeling and wound repair after inflammation has resolved, which can be pathological in the development of fibrosis in the lungs.…”
Section: Evs In Inflammatory Lung Diseasesmentioning
confidence: 99%